2021
DOI: 10.1152/ajplung.00304.2020
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxia and modulation of pulmonary vascular and immune responses in COVID-19

Abstract: Oxygen is the most commonly used therapy in hospitalized patients with COVID-19. In those patients who develop worsening pneumonia and acute respiratory distress syndrome (ARDS), high concentrations of oxygen may need to be administered for prolonged time periods, often together with mechanical ventilation. Hyperoxia, although lifesaving and essential for maintaining adequate oxygenation in the short-term, may have adverse long-term consequences upon lung parenchymal structure and function. How hyperoxia per s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 47 publications
2
37
0
4
Order By: Relevance
“…Significantly, we found a persistent reduction in DLCO over the study period, consistent with earlier reports (E et al, 2021). Low DLCO could be caused by interstitial changes or pulmonary vascular abnormalities following COVID-19 infections (Lang et al, 2020;Patel et al, 2020;Hanidziar and Robson, 2021). Our study has shown that up to a third of COVID patients still have evidence of defect DLCO 1 year after discharge (Wu et al, 2021), although longer term follow-up with a larger cohort will be required to confirm this observation.…”
Section: Discussionmentioning
confidence: 56%
“…Significantly, we found a persistent reduction in DLCO over the study period, consistent with earlier reports (E et al, 2021). Low DLCO could be caused by interstitial changes or pulmonary vascular abnormalities following COVID-19 infections (Lang et al, 2020;Patel et al, 2020;Hanidziar and Robson, 2021). Our study has shown that up to a third of COVID patients still have evidence of defect DLCO 1 year after discharge (Wu et al, 2021), although longer term follow-up with a larger cohort will be required to confirm this observation.…”
Section: Discussionmentioning
confidence: 56%
“…Lung diffusion impairment could be attributable to lung epithelial damage, or interstitial or pulmonary vascular abnormalities. [30][31][32] Lung structural abnormality during late recovery of SARS was associated with the lung diffusion impairment; 33 however, the association during convalescence after COVID-19 was unclear. We undertook an initial exploratory analysis on the basis of a small group of patients and found that lung imaging patterns at 12 months might be associated with lung diffusion impairment, which should be confirmed in a larger sample study.…”
Section: Discussionmentioning
confidence: 99%
“…Among the main respiratory functional changes, alteration in gas transfer measured by diffusing capacity for carbon monoxide (D LCO ) has been documented up to 12 weeks of follow-up [13,[86][87][88]. D LCO alteration could be associated with interstitial and vascular damage, secondary to acute infection [89,90]. These features may depend on the severity of the disease during the acute COVID-19 [91][92][93].…”
Section: Discussionmentioning
confidence: 99%